2021
DOI: 10.3390/s21041315
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing SSVEP-Based Brain-Computer Interface with Two-Step Task-Related Component Analysis

Abstract: Among various methods for frequency recognition of the steady-state visual evoked potential (SSVEP)-based brain-computer interface (BCI) study, a task-related component analysis (TRCA), which extracts discriminative spatial filters for classifying electroencephalogram (EEG) signals, has gathered much interest. The TRCA-based SSVEP method yields lower computational cost and higher classification performance compared to existing SSVEP methods. In spite of its utility, the TRCA-based SSVEP method still suffers fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Due to the development of BCI detection algorithm, the short-time detection performance of SSVEP-BCIs has almost reached its limit. It is significant to design a more user-friendly BCI paradigm based on the characteristics of existing EEG signal algorithms [25], [35], [36]. good BCI stimulation paradigm can be defined with the following features: (1) Visual fatigue caused by stimulation can be accepted by most users; (2) it can be easily transplanted to various control scenes; (3) it can well adapt to existing EEG detection algorithms; (4) it supports encoding a large number of operation instructions.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the development of BCI detection algorithm, the short-time detection performance of SSVEP-BCIs has almost reached its limit. It is significant to design a more user-friendly BCI paradigm based on the characteristics of existing EEG signal algorithms [25], [35], [36]. good BCI stimulation paradigm can be defined with the following features: (1) Visual fatigue caused by stimulation can be accepted by most users; (2) it can be easily transplanted to various control scenes; (3) it can well adapt to existing EEG detection algorithms; (4) it supports encoding a large number of operation instructions.…”
Section: Discussionmentioning
confidence: 99%
“…This constrained optimization problem can be transformed into a Rayleigh-Ritz eigenvalue problem by Covariance maximization [35]. Similar to filter bank canonical correlation analysis, applying filter bank analysis to TRCA can significantly improve performance [36]. The filter bank analysis is applied to the EEG data for decomposing it into 𝑁 𝑘 sub-bands.…”
Section: E Trca-based Methodsmentioning
confidence: 99%
“…Many SSVEP decoding algorithms exist for this purpose and have been widely studied [6]–[9]. It is often reported that including historical ‘training’ or calibration data - whether subject specific or across multiple subjects - offers significantly superior decoding performance compared to inference on instantaneous test signals (as with standard CCA) [7]–[9].…”
Section: Introductionmentioning
confidence: 99%